Dietary betaine supplementation improves growth performance, digestive function, intestinal integrity, immunity, and antioxidant capacity of yellow-feathered broilers. Issue 1 (1st January 2021) - Song, Yuduo; Chen, Rui; Yang, Mi; Liu, Qiang; Zhou, Yanmin; Zhuang, Su
Abstract: To investigate the effects of dietary betaine supplementation on the growth performance, digestive function, intestinal integrity, immunity, and antioxidant capacity of yellow-feathered broilers, a total of 400 one-day-old female yellow-feathered broilers were randomly allocated into 5 dietary treatments with 8 replicates of 10 chicks each, and fed a basal diet supplemented with 0 (control group), 125, 250, 500 and 1000 mg/kg betaine for 74 days, respectively. During the 1–37 days and 1–74 days, betaine linearly increased ( p  < .05) average daily gain, and decreased ( p  < .05) daily feed intake and feed conversion ratio. At 37 days, betaine linearly increased ( p  < .05) the apparent utilisation of crude protein, dry matter, and ether extract, jejunal digesta amylase and trypsin activities, villus height of jejunum and ileum, and ileal secretory immunoglobulin A content, glutathione peroxidase activity, and claudin-1 mRNA abundance, and linearly decreased ( p  < .05) serum D-lactate content and diamine oxidase activity, jejunal malondialdehyde content and nuclear factor kappaB mRNA abundance, ileal toll-like receptor 4 and myeloid differentiation factor 88 mRNA abundance. At 74 days, betaine linearly increased ( p < . 05) pancreatic lipase activity, jejunal glutathione peroxidase activity, and ileal glutathione content, and linearly decreased ( p  < .05) serum diamine oxidase activity and ileal malondialdehyde content. In conclusion, dietary supplementation with betaine improved growth performance, digestive function, intestinal mucosal barrier integrity, immune function, and antioxidant capacity of yellow-feathered broilers, and its optimal dosage in this study is 1000 mg/kg. HIGHLIGHTS: Betaine improved growth performance. Betaine increased digestive function. Betaine enhanced intestinal antioxidant capacity. Betaine improved intestinal integrity and barrier function. Betaine improved intestinal immunity.